From beauty to desire, from desire to death: approach to the poetic work by L. A. de Villena: 1971-1984 - García Rodríguez, Francisco Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The unavoidable colaboration between Literary Criticism and Literary History is clear, among some other research fields, in the establishment made by Literary Criticism of a canon of authors, works, tendencies and generations that, once considered as novelties in comparison with previous times, mean an important renewal.This essay about Luis Antonio de Villena's poetic work between 1971 and 1984 has been written within this kind of research. This work is a fundamental contribution to the Spanish current poetry becausc of the treatment as well as the originality of its subjects.Following a method based on the establishment of the textual topics in Villena's work, those ones are understood under generational criteria and the evolution of the author's poetic work.
Keywords: Luis Antonio de Villena; poetry; beauty; desire; death